Reovirus directly engages integrin to recruit clathrin for entry into host cells - Melanie Koehler (Nature Portfolio, 2021)
Reovirus endocytosis depends on junctional adhesion molecule A (JAM-A) and β1 integrin binding. Here, Koehler et al. use single-virus force spectroscopy and confocal microscopy to demonstrate a direct interaction between reovirus and β1 integrins via viral capsid protein λ2, which promotes clathrin recruitment to cell-bound reovirus.